Knowledge, practice and factors influencing intake of junk food among the students of HAMS nursing college. - Bhattarai, Bijaya Ghimire (2015)
ABSTRACT: This Descriptive study entitled " Knowledge, practice and factors influencing intake of junk food among students of hams nursing colleges" was carried out with the objective of to identify the knowledge and practices regarding junk food among the young girls. This study was conducted in Hams Nursing College Budhanagar, Kathmandu Nepal. The population of the study was students who studied in PCL 1st ,2nd and 3rd year. the total 120 students were selected by using systemic random sampling technique . A pre-tested semi structured questionnaire was used to measure the research variables. The data obtained was analyzed by using descriptive statistics such as frequency and percentage. The study findings revealed that majority of respondents(50%) were between 19-22 years of age, and (66%) live in nuclear family . All most all respondents (92%) knew about balance diet among them only(80%) had good knowledge about it, (86.5%) respondents knew about the junk food items, (23%) reported junk food is a packed food said junk food is not alternative food for healthy food. The main source of getting information about junk food followed by advertisement (44%). Students were known about the effects of junk food, among them (40%0 said obesity,(21%) diabetes mellitus & (9%) heart disease.(63%) faced various problems after consumption of junk food. Majority of them (40%) faced diarrhea,(29%) stomach pain, vomiting (2050 and food poisoning (11%). Majority of respondents (37%) reported that they didn't improve their diet due to lack of time. practice of respondent regarding junk food revealed that all the respondents were consumed junk food in their daily life. Most of them(41%) preferred noodle, (42%) respondents spent rs 20-40 daily on junk food purchase, 77% commonly preferred junk food in morning and maximum respondents that their junk food habit increased after left home. in conclusion, most of the college student have some knowledge about the junk food and its possible harmful effects but despite h=this knowledge, all the college student consumed junk food. Hence, it is necessary to include in the course of college student depth and need to formulate the policy regarding the food consumption